The role of social media to make singers in China—One case study of TF BOYS - Zhang, Mengru (2017)
In Web 2.0, social media spread to our daily life gradually. We gain information and news or make friends with that. In fact, social media also has some business advantages because it could spread information to people and cause great effects to people in short time. fans economy has been very popular in China nowadays, which means that the idol image is designed to cater to target fans and idol has become a business product. As the advantage of social media in business operation, it has already been used to make business idol. However, many researches focus on the role of idol and fans in fans economy or marketing strategies more, but lack of the role of social media exploration in practical execution. Marketing strategies are truly deserved to research, but the execution process is also important as the poor execution also will cause failure. Social media plays an important role in China to make idol, especially in practical execution. Here, we want to explore the role of social media to make singers in China and use a Chinese band called TF BOYS as a case study. In other words, we would like to research the executive process with social media to make singers — a case study of TF BOYS. The qualitative research method will be used as we would like to know an in-depth understanding of consumer behavior. In detail, in-depth interview and observation would be adopted. We want to interview 20 TF BOYS fans and ask them questions with AISAS model. AISAS is the consumer behavior steps that includes attention, interest, search, action and share. In findings, we found that social media plays a vital role in the five steps, especially search, action and share steps. Fans could search TF BOYS information on fans station on social media and buy related products online. In sharing step, they do not just share related products, but share passion of idol online with other fans. In a word, fans passion of TF BOYS is transferred to the purchasing power by correct digital marketing strategy and social media spread. We anticipate that the topic, the role of social media in fans economy, still has plenty of space to research, especially the psychological changing of fans. In practical execution, the online activities held by fans executor instill the belief about TF BOYS seriously to fans, which could strengthen the passion of them.